Shelfbreak Upwelling in the Western Beaufort Sea, Zooplankton Abundance data, August 2018. - Celia Gelfman; Robert Campbell; Carin Ashjian (Arctic Data Center, 2022)
Atmospherically-forced wind-induced upwelling along the shelf break leads to enhanced feeding opportunities for intermediate links in the pelagic ecosystem that in turn sustain the exploitation of this environment by animals such as beluga, seabirds, and seals. The Beaufort Sea shelf break is a hotspot for upper trophic level animals because elevated numbers and biomass of large, high-energy zooplankton (e.g., lipid-rich copepods, euphausiids) are regularly upwelled from deeper water onto the shelf during winds from the east, retained there by frontal features when upwelling relaxes, and exploited by bowhead whales, seabirds, and forage fish that in turn are prey for piscivorous marine mammals, such as beluga whales. The zooplankton abundance data were collected to measure upwelling impacts to the Beaufort shelf break community structure. Data were acquired as part of the National Science Foundation (NSF)-funded project "The Importance of Shelf Break Upwelling to Upper Trophic Level Ecology in the Western Beaufort Sea". Data from net tows within the box 165 West (W) - 145 W, 69 North (N) - 72N between 8 and 23 August 2018.